An Analysis of Students’ Perception and Motivation In Learning English By Using Google Classroom During Covid-19 Pandemic In The Eleventh Graders At Sma N 1 Kec. Payakumbuh - Engsha Refal Khrismaninda; Refnaldi Refnaldi (Journal of English Language Teaching, 2021)
During COVID-19 pandemic, many schools are required to conduct distance learning or online learning. Google classroom is one of the learning media that can be used during a pandemic. The application can be a medium for learning English in various schools. It can be a communication tool for students and teachers during online learning activities. This study aims to see and analyze how students' perceptions and motivations in learning English during the Covid-19 pandemic. As well as measuring the positive or negative perceptions of students and the level of student motivation. The design of this research was descriptive quantitative. the instrument of this research were the questionnaires and interview. The questionnaire containing 73 items was distributed to 235 students in order to get data. The researcher found that students had a positive perception of google classroom as an online learning medium with a mean of 2.64.However, in its use in English skills lessons, students have negative perceptions with a mean of 2,47. In addition, the researchers also found that students are less motivated to learn English when using Google Classroom with a mean of 2.39. in conclusion, although students have a positive perception of google classroom in learning English, students are still less motivated to learn by using google classroom.